Long-Term Outcomes and Cost-Effectiveness of an Internet-Based Self-Help Intervention for Social Anxiety Disorder in University Students: Results of a Randomized Controlled Trial - Kählke, Fanny; Buntrock, Claudia; Smit, Filip; Berger, Thomas; Baumeister, Harald; Ebert, David Daniel (Depression and Anxiety, 2023)
Social anxiety disorder (SAD) is widespread among university students and is associated with high costs for the society. While unguided internet- and mobile-based interventions (IMIs) may have short-term effects in reducing SAD symptoms, evidence for their long-term efficacy and cost-effectiveness is still limited. The aim of this study is to examine the 6-month outcomes of an IMI for university students with SAD. Participants were recruited via mass mails sent to enrolled students and included if they were at least 18 years old, met the diagnostic criteria of SAD in a structured clinical interview for DSM-IV axis I disorders (SCID-I), and provided written informed consent. In a prospective study designed as a two-armed randomized-controlled trial, 200 students (mean age 26.7 years) diagnosed with SAD were randomly assigned to an IMI or a waitlist control (WLC) condition. The IMI consisted of nine weekly sessions based on the cognitive-behavioral treatment model for social phobia by Clark and Wells. The primary outcome was SAD symptom severity assessed via the Social Phobia Scale (SPS) and the Social Interaction Anxiety Scale (SIAS). A health economic evaluation from a societal and healthcare perspective examined the costs related to the symptom-free status and quality-adjusted life years (QALYs) gained. Statistically significant differences in SAD symptom severity previously found at posttreatment favoring the IMI were maintained at a 6-month follow-up [SIAS (Cohen’s d=0.59; 95% CI, 0.30, 0.87) and SPS (Cohen’s d=0.83; 95% CI, 0.54, 1.1)]. From a societal perspective, at a willingness to pay (WTP) of €0, the intervention was found to have a 92% and 93% probability of cost-effectiveness compared with the WLC per symptom-free status and QALY gained, respectively. From a healthcare perspective, the likelihood of cost-effectiveness of the intervention was 97% per symptom-free status at a WTP of €1000 (US$1326) and 96% per QALY gained at a WTP of €6000 (US$7956). This IMI is effective in treating university students with SAD and has an acceptable likelihood of cost-effectiveness compared with WLC from a societal perspective. This intervention can be integrated into university healthcare to reach students with SAD as it is scalable, shows a high probability of cost-effectiveness, and overcomes known treatment barriers. This trial is registered with DRKS00011424.